2020
DOI: 10.1016/j.rpor.2020.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on the performance of a radiation oncology department at a major comprehensive cancer centre in Poland during the first ten weeks of the epidemic

Abstract: The outbreak of SARS-CoV-2 coronavirus rapidly altered radiotherapy service delivery around the world. Aim The main objective of this study was to assess the impact of precautionary measures implemented in response to the COVID-19 pandemic on the performance of a radiation oncology departments and on mitigation the risk of COVID-19 contagion between and among patients and staff. Methods The study period was from March 15 until May 22, 2020. We evaluated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 13 publications
2
13
0
1
Order By: Relevance
“…However, the real impact of the COVID-19 pandemic in radiation oncology departments in terms of the number of patients and delays in radiation treatments, as well as the number of professionals and patients with COVID-19 infection has been rarely reported. Ma-licki et al [7] analyzed the impact of precautionary measures in response to COVID-19 in a large Radiation Oncology center in Poland and found a reduction of 37% in the number of patients treated daily, which is similar to the 27% observed in our series. These authors [7] found an incidence of 2 out of 159 tested staff members with positive PCR (1.2%) compared to 16.6% in our department.…”
Section: Low Prioritysupporting
confidence: 86%
See 1 more Smart Citation
“…However, the real impact of the COVID-19 pandemic in radiation oncology departments in terms of the number of patients and delays in radiation treatments, as well as the number of professionals and patients with COVID-19 infection has been rarely reported. Ma-licki et al [7] analyzed the impact of precautionary measures in response to COVID-19 in a large Radiation Oncology center in Poland and found a reduction of 37% in the number of patients treated daily, which is similar to the 27% observed in our series. These authors [7] found an incidence of 2 out of 159 tested staff members with positive PCR (1.2%) compared to 16.6% in our department.…”
Section: Low Prioritysupporting
confidence: 86%
“…Ma-licki et al [7] analyzed the impact of precautionary measures in response to COVID-19 in a large Radiation Oncology center in Poland and found a reduction of 37% in the number of patients treated daily, which is similar to the 27% observed in our series. These authors [7] found an incidence of 2 out of 159 tested staff members with positive PCR (1.2%) compared to 16.6% in our department. This difference is probably due to the fact that in our center PCR was only performed in individuals with symptoms or risky contact, as well as the higher incidence of COVID-19 infection in our region.…”
Section: Low Prioritysupporting
confidence: 86%
“…Clinical radiotherapy practice was indirectly impacted globally with several reports 23 , 24 , 25 , 26 , 27 , 28 indicating a decline in patient volumes, although almost all departments were operational during the pandemic. The rapidly evolving situation 29 resulted in the regular release of recommendations from national and international authorities including the International Society of Radiographers and Radiological Technologists (ISRRT), National Cancer Research Institute (NCRI – UK), European Society for Radiotherapy and Oncology (ESTRO) and the American Society for Radiation Oncology for safe clinical care of cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Mumbai was the worst affected city during the COVID 19 pandemic in India (12). In the first phase of the pandemic, also corresponding to nationwide lockdown, the gynaecology radiation oncology unit treated at one-third of its capacity which is similar to the rate reported in cancer hospitals in the west as a result of reorganisation of infrastructural and human resources (13)(14)(15)(16)(17). During this period as seen in our results approximately 25-30% patients decided not to receive further treatment due to fear of infection and challenges posed due to nationwide lockdown reducing patients' ability to travel for 8-week treatment.…”
Section: Discussionmentioning
confidence: 55%